Evaluasi Efektivitas Instalasi Pengolahan Air Limbah (IPAL) pada Industri Pengolahan Makanan di Kabupaten Sidoarjo - Delia Anisa Putri; Mohamad Mirwan (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
iquid waste produced by the food industry has complex characteristics that depend on production capacity. Liquid waste treatment is carried out physically, chemically, and biologically to reduce the concentration of pollutants that pose environmental problems. PT. X is one of the companies that produces food products. The company has been implementing an environmental management system, particularly wastewater treatment, using WWTP technology. The research aims to assess the performance of liquid wastewater treatment processes at PT. X. The research method used is descriptive, with data collection through direct observation and sampling at the WWTP outlet of PT. X. After testing, the research results show that all main parameters produced by PT. X's WWTP comply with the quality standards of the East Java Governor Regulation No. 72 of 2013. Overall, the WWTP performance remains good.